Evaluating tactile feedback in robotic surgery for potential clinical application using an animal model - Wottawa, Christopher R.; Genovese, Bradley; Nowroozi, Bryan N.; Hart, Steven D.; Bisley, James W.; Grundfest, Warren S.; Dutson, Erik P. (Surgical endoscopy, 2016)
Introduction The aims of this study were to evaluate (1) grasping forces with the application of a tactile feedback system in vivo and (2) the incidence of tissue damage incurred during robotic tissue manipulation. Robotic-assisted minimally invasive surgery has been shown to be beneficial in a variety of surgical specialties, particularly radical prostatectomy. This innovative surgical tool offers advantages over traditional laparoscopic techniques, such as improved wrist-like maneuverability, stereoscopic video displays, and scaling of surgical gestures to increase precision. A widely cited disadvantage associated with robotic systems is the absence of tactile feedback. Methods and procedure Nineteen subjects were categorized into two groups: 5 experts (six or more robotic cases) and 14 novices (five cases or less). The subjects used the da Vinci with integrated tactile feedback to run porcine bowel in the following conditions: ( T 1: deactivated tactile feedback; T 2: activated tactile feedback; and T 3: deactivated tactile feedback). The grasping force, incidence of tissue damage, and the correlation of grasping force and tissue damage were analyzed. Tissue damage was evaluated both grossly and histologically by a pathologist blinded to the sample. Results Tactile feedback resulted in significantly decreased grasping forces for both experts and novices ( P < 0.001 in both conditions). The overall incidence of tissue damage was significantly decreased in all subjects ( P < 0.001). A statistically significant correlation was found between grasping forces and incidence of tissue damage ( P = 0.008). The decreased forces and tissue damage were retained through the third trial when the system was deactivated ( P > 0.05 in all subjects). Conclusion The in vivo application of integrated tactile feedback in the robotic system demonstrates significantly reduced grasping forces, resulting in significantly less tissue damage. This tactile feedback system may improve surgical outcomes and broaden the use of robotic-assisted minimally invasive surgery.